Firewood, smoke and respiratory diseases in developing countries: The neglected role of outdoor cooking - Jörg Langbein (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Smoke from cooking in the kitchen is one of the world's leading causes of premature child death, claiming the lives of 500,000 children under five annually. This study analyses the role of outdoor cooking and the prevalence of respiratory diseases among children under five years by means of probit regressions using information from 41 surveys conducted in 30 developing countries from Asia, Africa and Latin America. I find that outdoor cooking reduces respiratory diseases among young children aged 0-4 by around 9 percent, an effect that reaches 13 percent among children aged 0-1. The results suggest that simple behavioral interventions, such as promoting outdoor cooking, can have a substantial impact on health hazards. – – Jährlich sterben ungefähr 500.000 Kinder im Alter von 0 bis 4 Jahren an den Folgen häuslicher Rauchpartikel, die beim Kochen mit Biomasse entstehen. Die vorliegende Studie nutzt Informationen aus 30 Ländern und dem Auftreten von Lungenatemwegserkrankungen bei Kindern unter 5 Jahren. Mit Hilfe einer Probit Regression wird gezeigt, dass eine Kochstelle außerhalb des Hauses das Auftreten von Lungenatemwegserkrankungen bei Kindern im Alter von 0 bis 4 um 9 Prozent reduziert und bei Kindern im Alter von 0-1 um 13 Prozent. Diese Ergebnisse lassen vermuten, dass einfache Verhaltensänderungen, wie zum Beispiel das Fördern von Kochstellen außerhalb des Hauses, einen wichtigen Einfluss auf gesundheitliche Risiken haben.
Keywords: Q53; I12; O13; 330; air pollution; health behavior; energy access